INFLATION, ECONOMIC GROWTH, NET LENDING/BORROWING, GENERAL GOVERNMENT FINAL CONSUMPTION EXPENDITURE (GGFCE), EXPORTS, AND IMPORTS ON TAX REVENUE: A PANEL STUDY OF ASEAN COUNTRIES, 2014–2022 - Mohammad Fadhilatul Isro’i; Herman Ernandi (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study aims to analyze the effects of inflation, economic growth, net lending/borrowing (NLB), general government final consumption expenditure (GGFCE), exports, and imports on tax revenue, measured by the tax-to-GDP ratio, across eight ASEAN countries. Method: Using annual panel data from 2014–2022 (N=8, T=9; 72 observations), the research applies panel regression supported by Chow, Hausman, and LM tests, which identify the Random Effects Model (REM) estimated through EGLS as the most appropriate specification. Hypotheses are examined using two-sided t-tests at a 5% significance level, with emphasis on p-values and R² statistics. Results: The findings indicate that NLB, GGFCE, and imports significantly influence tax revenue, whereas inflation, economic growth, and exports show no significant effects. The model demonstrates moderate explanatory power with R² of approximately 0.46 and Adjusted R² of 0.41. Novelty: This study contributes empirical insight into the fiscal dynamics of ASEAN by integrating macroeconomic, fiscal, and trade variables simultaneously and by identifying government financial behavior and import activity as key determinants of the regional tax base—an area underexplored in prior cross-country tax performance research.